The impact of vat in the fight against the informal economy in Kosovo - Haziri, Artan; Maksutaj, Mimoza Bytyqi; Maksutaj, Nazmi (Edelweiss Applied Science and Technology, 2025)
This paper explores the role of Value Added Tax (VAT) in tackling the informal economy in Kosovo, focusing on how tax reforms can support the shift toward a more formal and transparent market. Drawing on ordinary least squares (OLS) regression, correlation analysis, and trend evaluation, the study examines the relationship between VAT revenues and economic growth, as measured by GDP. While the statistical findings point to a weak positive correlation (0.1014), suggesting a limited direct effect of VAT on GDP, the broader analysis highlights deeper structural issues. Challenges such as high compliance costs, complex tax procedures, and limited institutional capacity continue to undermine the effectiveness of VAT as a tool for formalization. The research argues that for VAT to make a meaningful difference, reforms must go beyond tax policy—requiring digital modernization, stronger enforcement, and efforts to build public trust. The study offers practical recommendations for policymakers, emphasizing the importance of simplifying tax compliance, improving tax administration, and encouraging formal participation in the economy. These measures are crucial for reducing informality and creating a more stable and transparent fiscal environment in Kosovo.